2006
DOI: 10.1364/oe.14.011870
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain analysis of periodic anisotropic media at oblique incidence: an efficient FDTD implementation

Abstract: We describe an efficient implementation of the finite-difference time-domain (FDTD) method as applied to lightwave propagation through periodic media with arbitrary anisotropy (birefringence). A permittivity tensor with non-diagonal elements is successfully integrated here with periodic boundary conditions, bounded computation space, and the split-field update technique. This enables modeling of periodic structures using only one period even with obliquely incident light in combination with both monochromatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 28 publications
(34 reference statements)
2
72
0
Order By: Relevance
“…Periodic molecular distribution with uniaxial anisotropy can be placed on the analysis regions. Polarization holograms have been simulated, and these results are consistent to with other theoretical [81,82] and experimental results [83]. The visualized optical propagation obtained from the simulations is especially useful for developments of optical devices.…”
Section: Anisotropic Gratingssupporting
confidence: 81%
“…Periodic molecular distribution with uniaxial anisotropy can be placed on the analysis regions. Polarization holograms have been simulated, and these results are consistent to with other theoretical [81,82] and experimental results [83]. The visualized optical propagation obtained from the simulations is especially useful for developments of optical devices.…”
Section: Anisotropic Gratingssupporting
confidence: 81%
“…The FDTD method can analyze anisotropic media such as liquid crystals (Kriezis & Elston, 1999, 2000Titus et al, 2001;Scharf, 2007). In addition, it has been reported that the FDTD method is suitable for characterizing anisotropic gratings recorded by vector holography (Oh & Escuti, 2006Ono et al 2008aOno et al , 2008b. Figure 9 schematically illustrates the model for the FDTD calculation in this study.…”
Section: Fdtd Methodsmentioning
confidence: 99%
“…We also assume Uniaxial Perfectly Matched Layer [37,38] (UPML) for the truncation in the z direction. The input plane wave source is excited in the structure following the schemes proposed in [23,39] for both continuous and time-limited pulsed waves.…”
Section: Theorymentioning
confidence: 99%
“…Following [29,39], we next eliminate the time-derivative terms ∂/∂t ⇔ jω by splitting the field variables:…”
Section: Basic Concepts Of Sf-fdtdmentioning
confidence: 99%